2016
DOI: 10.1017/cem.2016.365
|View full text |Cite|
|
Sign up to set email alerts
|

Can an emergency department clinical “triggers” program based on abnormal vital signs improve patient outcomes?

Abstract: Background: Because abnormal vital signs indicate the potential for clinical deterioration, it is logical to make emergency physicians immediately aware of those patients who present with abnormal vital signs. Objectives: To determine if a clinical triggers program in the emergency department (ED) setting that utilized predetermined abnormal vital signs to activate a rapid assessment by an emergency physician-led multidisciplinary team had a measurable effect on inpatient hospital metrics. Methods: The study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Recent work has focused on the development of predictive tools based on ED vital signs to assist EPs in identifying patients at risk for decompensation 8,9. One example, the PeRRT (Predicting Early Rapid Response Team) score, incorporates vital signs (among other data) to predict which patients would trigger a rapid response activation during the first 12 hours of admission 10.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has focused on the development of predictive tools based on ED vital signs to assist EPs in identifying patients at risk for decompensation 8,9. One example, the PeRRT (Predicting Early Rapid Response Team) score, incorporates vital signs (among other data) to predict which patients would trigger a rapid response activation during the first 12 hours of admission 10.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-two studies were single site studies [19,20,[32][33][34][35][36][37][38][39][40][41][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. The countries of origin were Turkey (n = 8) [33, 34, 37-39, 42, 45, 48], United States (n = 3) [41,43,49], United Kingdom (n = 3) [44,50,51], Australia (n = 3) [19,20,57], China (n = 3) [35,60,62], Italy (n = 2) [58,61], Indonesia (n = 2) [46,47] and one study each from Finland [32], De...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Only six studies explicitly reported the response to ED patients identified as deteriorating [19,20,44,49,52,58].…”
Section: Response To Clinical Deterioration In Ed Patientsmentioning
confidence: 99%
See 2 more Smart Citations